Maternal and Microorganism Characteristics Cannot Predict Adverse Outcome in Pregnancies Complicated With Urinary Tract Infection. Issue 1 (January 2021) - Orgul, Gokcen; Uyanik, Esra; Sancak, Banu; Beksac, M. Sinan
Abstract : Background: Previous studies revealed different results on the impact of urinary tract infection on pregnancy outcomes. Inconsistent data on adverse outcomes such as preterm delivery, low birth weight, and intrauterine growth restriction (IUGR) are reported in several studies. Methods: Microorganisms were classified into 4 groups; Enterobacteriaceae, gram-positive cocci, fungi and others. Adverse pregnancy outcome was defined in the presence of IUGR, preterm delivery, low birth weight, and low appearance, pulse, grimace, activity, and respiration score. Adverse and no adverse outcome groups were compared. Results: The total number of women with a positive urinary culture was 186. The most common isolated microorganism was Escherichia coli (n = 111, 59.7%). Among E. coli isolates, resistance was most common to ampicillin and trimethoprim sulfamethoxazole. The mean gestational week was 23.3 ± 1.12 for the urinary tract infection onset time and recurrence rate was 11.8% (n = 22). Oral antibiotics were prescribed to 164 outpatient women and hospitalization was required in 22 cases (11.8%). The rates of IUGR, low birth weight, low appearance, pulse, grimace, activity, and respiration, and preterm delivery were 11.8%, 11.3%, 6.9%, and 17.7%, respectively. There were 137 women (73.7%) in no adverse outcome group, whereas 49 women (26.3%) were in adverse outcome group. There was no significant difference in terms of bacteria group and maternal characteristics between 2 groups ( P < 0.05 for all). Conclusions: Maternal and microorganism characteristics are similar in pregnancies complicated with urinary infections in terms of adverse outcome. It is not possible to predict the ongoing pregnancy course by identifying maternal and microbiological features.